2018
DOI: 10.1590/0100-29452018846
|View full text |Cite
|
Sign up to set email alerts
|

Bocaiuva jelly: preparation, physicochemical and sensory evaluation

Abstract: Bocaiuva cultivation, mainly in Mato Grosso do Sul, has a strong socio-economic and environmental appeal. Bocaiuva pulp is rich in nutrients and has antioxidant action, and its use in the formulation of jellies minimizes post-harvest losses and provides market with a product with high nutritional value throughout the year. The aim of this work was to elaborate and chemically and sensorially evaluate jellies produced with bocaiuva pulp (Acrocomia aculeata (Jacq.) Lodd ex Mart) of two morphotypes, orange and yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
0
1
Order By: Relevance
“…The lipid content of fresh macaúba pulp was 15.47±1.01 g 100 g -1 , which is similar to the 13.96-15.77% found by Silva et al (2018) in the pulp of macaúba fruits obtained in the state of Mato Grosso do Sul (13.96-15.77%) and lower than the 44.2±0.2% found by Queiroz (2016) in macaúba fruits in Rio Largo -AL.…”
Section: Resultssupporting
confidence: 71%
“…The lipid content of fresh macaúba pulp was 15.47±1.01 g 100 g -1 , which is similar to the 13.96-15.77% found by Silva et al (2018) in the pulp of macaúba fruits obtained in the state of Mato Grosso do Sul (13.96-15.77%) and lower than the 44.2±0.2% found by Queiroz (2016) in macaúba fruits in Rio Largo -AL.…”
Section: Resultssupporting
confidence: 71%
“…However, during storage, the moisture content increased from 28.09% at time 0 to 34.17% at 120 days, indicating possible permeability to water vapor in the packages. Silva et al (2018) evaluated bocaiuva jelly with passion fruit and found a moisture content of 27.19%, close to time 0 of the present study. In sweets, moisture gain can make the product sticky and cause changes in color, flavor, and aroma (Sarantopoulos et al, 2001), which was not observed in the mass candy of bocaiuva during storage.…”
Section: Physicochemical Stabilitysupporting
confidence: 81%
“…When positive, the values de a * and b * represent tones of red and yellow. The color of the bocaiuva pulp was evaluated by Silva et al (2018), who reported values of 42.18, 10.95, and 40.22 for L * , a * , and b * , respectively, higher than those found. The difference between values of a * and b * can be due to processing that reduced the level of carotenoids, a bioactive sensitive to heat (Koop et al, 2022), which gives the pulp an orange color.…”
Section: Physicochemical Stabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…These authors observed that fruits with As shown in Table 3, the formulations with the highest pulp concentration were the ones that showed the best results for crude fibers. Fiber values found for guapeva jams were higher than those described by Silva et al (2018) for yellow and orange bocaiuva jams, which presented concentrations of 0.46 and 0.66 g. 100 g -1 , respectively.…”
Section: Resultscontrasting
confidence: 62%